Assessment of Malnutrition among Children Presenting in a Nutrition Center in Gimbichu, Ethiopia - M. Ascensión Olcina Simón; Jose M. Soriano; María Morales- (MDPI AG, 2023)
Nowadays, Ethiopia has several problems affecting children below 5 years of age, resulting in low life expectancies. Our group carried out a study to calculate the presence of malnutrition as wasting, stunting underweight, and BMI-for-age in children presenting in a nutrition center in a rural Ethiopian village in the Oromia region according to WHO guidelines. Our results demonstrated that they had moderate chronic malnutrition or stunting from 1 to 2 years of age, affecting their life, their parents, their community/household, and their country. In our viewpoint, the solution for this situation will require a global focus on several levels, including individual, family, community, and country, the last being with the help of new health policies focused on short-, medium-, and long-term strategies with multi- and interdisciplinary approaches.